Delivery of health care at the end of life in cancer patients of four swiss cantons: a retrospective database study (SAKK 89/09) - Matter-Walstra, Klazien W (BioMed Central, 2014)
BACKGROUND: The use of cancer related therapy in cancer patients at the end-of-life has increased over time in many countries. Given a lack of published Swiss data, the objective of this study was to describe delivery of health care during the last month before death of cancer patients. METHODS: Claims data were used to assess health care utilization of cancer patients (identified by cancer registry data of four participating cantons), deceased between 2006-2008. Primary endpoints were hospitalization rate and delivery of cancer related therapies during the last 30 days before death. Multivariate logistic regression assessed the explanatory value of patient and geographic characteristics. RESULTS: 3809 identified cancer patients were included. Hospitalization rate (mean 68.5%, 95% CI 67.0-69.9) and percentage of patients receiving anti-cancer drug therapies (ACDT, mean 14.5%, 95% CI 13.4-15.6) and radiotherapy (mean 7.7%, 95% CI 6.7-8.4) decreased with age. Canton of residence and insurance type status most significantly influenced the odds for hospitalization or receiving ACDT. CONCLUSIONS: The intensity of cancer specific care showed substantial variation by age, cancer type, place of residence and insurance type status. This may be partially driven by cultural differences within Switzerland and the cantonal organization of the Swiss health care system.